Ethnomathematics-Based Geometry Modules to Enhance Problem-Solving Skills of Islamic Junior High School Students - Ifada Novikasari; Lisa Awalia; Noor Elebiary (Institut Agama Islam Negeri Imam Bonjol Padang, 2025)
This study investigates the effectiveness of ethnomathematics-based learning in enhancing ninth-grade students’ mathematical problem-solving skills in geometry at an Islamic junior high school. A quasi-experimental design with pre-test and post-test was employed, involving 47 students divided into an experimental group (n = 24) and a control group (n = 23). The experimental group received instruction integrating culturally relevant contexts, while the control group received teacher-centered expository instruction. Problem-solving skills were assessed through validated tests targeting comprehension, strategy formulation, execution, and evaluation, and analyzed using normalized gain (N-Gain) and independent-samples t-tests. Results indicated that the experimental group achieved significantly higher N-Gain scores than the control group, with a large effect size, demonstrating that ethnomathematics-based learning effectively fosters higher-order problem-solving abilities. These findings suggest that embedding cultural contexts in mathematics instruction provides a more engaging and enhancing students’ problem-solving skills.